Poverty-focused social accounting matrices for Tanzania - Thurlow, James; Wobst, Peter (International Food Policy Research Institute, 2003)
The development of effective and sustainable economic policies for Tanzania requires access to appropriate databases. One such database is a social accounting matrix (SAM) that details the structure of the entire economy, taking into account the patterns of production and demand, and various institutional relationships. Prior to this study the most recent SAM for mainland Tanzania was for 1992 and was based on past household budget and labor force surveys. Following the release of newer versions of these two surveys as well as a new input-output table for 1992, it is desirable to construct a new SAM for the country. Furthermore, given that Tanzania is committed to reducing national poverty, it is necessary that this new SAM is able to address questions related to poverty and inequality.